Conscientious objection to vaccination - Giubilini, A; Clarke, S; Walker, M (Wiley, 2016)
People refuse vaccines for themselves or for their dependants for a variety of reasons. These include the beliefs that vaccines cause health problems, that they are not really effective, that they are manufactured in unsafe ways, and that diseases are better dealt with by other means. There are also people who decide not to vaccinate out of a selfish desire to free-ride on the herd immunity achieved by the vaccinations of others (Navin 2013b; May 2005). Still others refuse to take vaccines or to vaccinate their dependants on conscientious grounds. Our focus in this paper is on vaccine refusal on conscientious grounds.